2010
DOI: 10.1637/9120-110309-resnote.1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Six Isolates of Beak and Feather Disease Virus from African Grey Parrots in Portugal

Abstract: Beak and feather disease virus (BFDV), a member of the genus Circovirus, was detected in six dead African grey parrots (Psittacus erithacus) in Portugal. The complete nucleotide sequences of these six BFDVs (PT05, PT08, PT08-2, PT08-3, PT09, and PT09-2) were determined and analyzed. The seven open reading frames (ORFs) described for other BFDVs were detected in all strains, except for PT05 and PT08, in which ORFs 4 and 7 are absent. Bayesian inference of phylogeny based on complete genomes of BFDVs isolated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…Over the course of this period, the focus in research has shifted from basic descriptions of patterns of presence or prevalence in populations towards studies investigating the processes of viral recombination, evolution and phylogenetics (e.g. [ 36 , 55 ]), the causes of outbreaks in wild populations (e.g. [ 28 , 40 ]), and the implications for improving the management of captive and wild populations.…”
Section: Discussionmentioning
confidence: 99%
“…Over the course of this period, the focus in research has shifted from basic descriptions of patterns of presence or prevalence in populations towards studies investigating the processes of viral recombination, evolution and phylogenetics (e.g. [ 36 , 55 ]), the causes of outbreaks in wild populations (e.g. [ 28 , 40 ]), and the implications for improving the management of captive and wild populations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported on BFDV infection in European captive psittacine breeding facilities (Bert et al , 2005; Henriques et al , 2010; Piasecki & Wieliczko, 2010; Rahaus & Wolff, 2003; Tomasek & Tukac, 2007), but in the majority of cases, rather than isolating and sequencing full viral genomes, only a fragment of Rep was amplified simply for the purpose of determining the presence of the viral infection. This is significant because various studies have shown that recombination is a major process contributing to the diversity of circoviruses in general (Cai et al , 2012; Cheung, 2009; Heath et al , 2004; Lefeuvre et al , 2009; Massaro et al , 2012; Varsani et al , 2010, 2011) and BFDV in particular.…”
Section: Introductionmentioning
confidence: 99%
“…It has to be noted that a suitable ATG start codon of the cap gene could only be identified in two strains, but an alternative start codon candidate (TTG) was localized in the remaining four strains, which allowed encoding of a protein of a length and with features common to other circoviruses. Lack of the canonical ATG start codon in the putative cap gene has been noted in many other circoviruses as well (Bassami et al, 1998;Phenix et al, 2001; de Kloet & de Kloet, 2004;Stewart et al, 2006;Todd et al, 2007;Henriques et al, 2010;Li et al, 2010;Robino et al, 2014). A highly basic N-terminal region of the protein and a bipartite nuclear localization signal were consistently identified supporting a possible function of the Cap protein in transporting the Rep protein into the nucleus (Heath et al, 2006).…”
Section: Discussionmentioning
confidence: 69%